2011
DOI: 10.1001/archdermatol.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Postherpetic Neuralgia After Combination Treatment With Gabapentin and Valacyclovir in Patients With Acute Herpes Zoster

Abstract: Objective: To evaluate the efficacy of treatment with gabapentin plus valacyclovir hydrochloride for the prevention of postherpetic neuralgia in patients with acute herpes zoster. Design:Uncontrolled, open-label study.Setting: A private dermatology clinic.Participants: Consecutive immunocompetent adults (age, Ն50 years) who presented with herpes zoster within 72 hours of vesicle formation with moderate to severe pain (Ն4 on the 10-point Likert scale) were recruited for study participation.Intervention: The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 46 publications
3
23
0
1
Order By: Relevance
“…Five systematic reviews, 4751 three RCTs7,35,52 and one cohort study12 contained evidence pertaining to the prevention of PHN; no meta-analyses did.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five systematic reviews, 4751 three RCTs7,35,52 and one cohort study12 contained evidence pertaining to the prevention of PHN; no meta-analyses did.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study,52 133 consecutive patients with acute HZ were enrolled in a private dermatology clinic and treated with valacyclovir and gabapentin at currently recommended dosages, with a lower incidence of PHN at 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers in an uncontrolled open-label study concluded that the combination of gabapentin and valacyclovir reduces the incidence of PHN [8]; however, although the gabapentin dose could be titrated up to 3600 mg/day, only a few patients reached that dose, and the median dose was 1085 mg/day for 34 days. This study was criticized because there was no control group; instead, the authors compared the incidence of PHN with historic control subjects described in a meta-analysis of six RCTs of antiviral agents used to treat acute zoster infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in a previous nonrandomized, noncontrolled experimental study reported the incidence of PHN was 20% [8]. Thus, we estimated a 45% incidence of PHN in the placebo group, based on its incidence in patients older than 50 years old with an average VAS pain score of 4 or more reported in a longitudinal study [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation